Re-examining the Objects of Mystical Reality - Abdullah, Sarena; Chung , Ah Kow (2014)
In the 1960s, when Malaysian artists seemed to be influenced by the Abstract Expressionist art movement of the West, a group of Malaysian artists known as the New Scene were interested in the “cerebral and impersonal”, analytical and constructivists aspects of art making. They were mostly interested in space, colour and materials that were exhibited in art exhibitions such as The New Scene, experiment ‘70, and Dokumentasi 72. Only the partnership of Redza and Sulaiman Esa, in their effort to provide an alternative aesthetic to the Abstract Expressionists, lasted. Both artists’ propositions on objects of real time and space were presented in the exhibition Towards a Mystical Reality in 1974 in which they took over the role of the critic by framing their own propositions, ideas, and concepts written in the manifesto published in conjunction with the exhibition. This essay attempts to discuss random objects without any aesthetic value selected by these artists as works of art by employing Dickie’s Institutional Theory. Furthermore, it will examine a few aspects from the theory that justify the exhibition and its content as art and thus argue that it has its own aesthetics that demand our own contextual analysis and understanding.